An E-Learning Experience: A written analysis based on my experience with primary school teachers in an e-Learning pilot project - Bose, Kabita (International Review of Research in Open and Distributed Learning, 2003)
This article reports the experience of an e-Learning pilot project selected by the Educational Technology Unit (EduTech) of the Centre for Academic Development (CAD), University of Botswana (UB). This e-Learning package was designed and delivered in connection with the three-credit course “Issues and Trends in Early Childhood Education” (EPI-642), which is required for the first year of the master’s program in the Department of Primary Education. The course was taught via a flexi-time, gradual, phase-by-phase transition from traditional face-to-face teaching to the electronic medium of an e-Learning lab (called SMART classroom). This course utilized a student centred e-Learning package that retained the learning qualities of traditional teaching, personal guidance, and mentoring, while seeking to enhance students’ research and computer skills.